A Development of a Management Information System for Home Appliance Repairing - Teo Peck May,; Hannani Aman, (Applied Information Technology And Computer Science, 2021)
Galaxy Ace Electronic Enterprise is a repair service centre has been taken as the case study of this project. Currently, this service centre applies and implements the manual system to manage its business operations. The problem of this service centre is the management for keeping the business records is poor and unsafe since all the documents are recorded in the logbook and paper, hence the data loss might be happened due to the missing or misplacing of paper. Therefore, a web-based home appliance repairing management system is developed to address these problems. The objectives of this project are to design, develop and test the home appliance repairing management system. The project scope focuses on helping this service centre to improve the management of all the business data. The system is developed by using the structured approach and waterfall model. The programming language used in this system is Hypertext Preprocessor (PHP), Hypertext Markup Language (HTML), Cascading Style Sheets (CSS). This system uses MySQL database server to store the data. The target users of this system are owner, staff, technician and customer. This system is expected to help the owner and staff to manage the customer records and repair requests easily and systematically. By using this system, the staff can create, retrieve, update and delete the business records. This system helps the service centre to automate its business activities effectively and manage data securely. This system also presents user-friendly functionality and provides convenience to the target users.